Toponymy and Naming Aspects of The Origins of Street and Alley Names at Lelewonu Niko’otano Village - Afore Tahir Harefa; Yuslinda Sari Zega; Puspa Fati Handayani Gulo (PT. Anagata Sembagi Education, 2024)
Lelewonu Niko'otano village based on the description of the origin of the name. The method used is descriptive qualitative. The data source in this research is a list of street and alley names in the village and documentation as well as the results of interviews with informants. This research was conducted with three stages, namely the data collection stage, the data analysis stage, and the presentation stage of the results of data analysis. Data collection was conducted using observation, interview, and documentation techniques documentation. Data analysis was carried out by classifying and analyzing it as a whole, i.e. classifying the names of roads in the village analyzing it as a whole, namely classifying street names in Lelewonu Niko’otano village based on the description of the origin of the name. Furthermore, analyzing the data based on description of the origin of the name, namely aspects of embodiment, societal aspects, and cultural aspects. The results of the data analysis are presented using informal methods. Based on the results of the analysis, toponymy and naming aspects of the origin of street names in Lelewonu Niko’otano village consist of: (1) Realization aspects, namely (a) naming based on the name of plants or flora and (b) naming based on the natural environment; (2) toponymy and aspects of naming the origin of street names in Lelewonu Niko’otano village based on the state of the natural environment; (2) the societal aspect, namely (a) naming based on warrior figures, (b) naming based on occupation or profession, and (d) societal aspects, namely based on occupation or profession, and (d) naming based on social interaction in the community; and none are included in (3) cultural aspects.